Spectrophotometric Methods for Simultaneous Estimation of Esomeprazole Magnesium and Domperidone from Pharmaceutical Dosage Form - PILLAI, S.; SINGHVI, I. (Asian Journal of Chemistry, 2010)
Three simple, accurate, economical and reproducible UV spectrophotometric methods for simultaneous estimation of two components drug mixture of domperidone and esomeprazole magnesium from combined capsule dosage form have been developed. First developed method involves formation and solving of simultaneous equations at 285.6 and 301.2 nm. Second method was developed making use of first order derivative spectroscopy using 300.8 and 311.2 nm as zero crossing points for estimation of domperidone and esomeprazole magnesium, respectively. Third method is based on two wavelength calculation, wavelengths selected for estimation of domperidone were 284.4 and 313.2 nm and for esomeprazole magnesium 275.2 and 293.2 nm. The results of analysis have been validated statistically and by recovery studies.